Processes of fault-controlled fluid-flow, alteration and gold mineralization at Sheba Mine, Barberton Greenstone Belt, South Africa - Pintos, Lucas (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.